Serum GFAP and NfL as disease severity and prognostic biomarkers in patients with aquaporin-4 antibody-positive neuromyelitis optica spectrum disorder - Schindler, Patrick; Grittner, Ulrike; Oechtering, Johanna; Leppert, David; Siebert, Nadja; Duchow, Ankelien S.; Oertel, Frederike Cosima; Asseyer, Susanna; Kuchling, Joseph; Zimmermann, Hanna; Brandt, Alexander Ulrich; Benkert, Pascal; et al. (Journal of neuroinflammation, 2021)
Neuromyelitis optica spectrum disorder (NMOSD) is a frequently disabling neuroinflammatory syndrome with a relapsing course. Blood-based disease severity and prognostic biomarkers for NMOSD are a yet unmet clinical need. Here, we evaluated serum glial fibrillary acidic protein (sGFAP) and neurofilament light (sNfL) as disease severity and prognostic biomarkers in patients with aquaporin-4 immunoglobulin (Ig)G positive (AQP4-IgG+) NMOSD.
Gesehen am 15.06.2021